ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIK MATERI LINGKARAN SISWA SMP BERDASARKAN GENDER - Maranata Sanglimbo Buranda; Martin Bernard (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The purpose of this study was to analyze the problem solving skills of junior high school students based on student gender. This research is descriptive qualitative. Data from the research results obtained from the results of writing written questions and the results of oral interviews of 14 students of class VIII from Waringin Middle School, Bandung. The instrument used is 3 numbers of material questions that are in accordance with indicators of cognitive aspects. The results of this study indicate that from the problem description given and from the results of interviews about problem solving abilities of junior high school students with female gender on average, it is better than the problem solving ability on average junior high school students have a way to solve while solving problems. So that researchers can conduct research using active student learning methods to get better results, and also be able to understand other factors related to problem solving problems of junior high school students, both male and female students.